2021
DOI: 10.1007/s00787-021-01739-0
|View full text |Cite|
|
Sign up to set email alerts
|

Families in the COVID-19 pandemic: parental stress, parent mental health and the occurrence of adverse childhood experiences—results of a representative survey in Germany

Abstract: Parenting during the COVID-19 pandemic is highly challenging, with parents having to meet various demands simultaneously. An increase in adverse childhood experiences (ACEs) has been widely predicted, but empirical evidence is still scarce. This study aimed to (1) generate representative data on pandemic-related stress, parental stress, general stress, parental subjective and mental health, and the occurrence of ACEs; (2) identify risk factors for an increase in ACEs, and (3) provide qualitative data on parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
301
2
22

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(388 citation statements)
references
References 37 publications
37
301
2
22
Order By: Relevance
“…Many of the children themselves had difficulties coping and developed abnormal behaviors (Wang G. et al, 2020), which impacted their parents (Calvano et al, 2021)-mothers and fathers alike-as indicated by our results. This is where the pandemic comes down to the concept of Seligman's learned helplessness from about four decades ago.…”
Section: Depressionsupporting
confidence: 61%
“…Many of the children themselves had difficulties coping and developed abnormal behaviors (Wang G. et al, 2020), which impacted their parents (Calvano et al, 2021)-mothers and fathers alike-as indicated by our results. This is where the pandemic comes down to the concept of Seligman's learned helplessness from about four decades ago.…”
Section: Depressionsupporting
confidence: 61%
“…3 Research in other settings has found that school closures directly impacted parental stress and well-being. 4 In our own qualitative research conducted as part of a national study of COVID-19 transmission and prevention in English primary and secondary schools, parents report an enhanced appreciation of the key role schools play in their children's health and social development, as well as in supporting their own well-being. Parents also reported that their children had an increased enthusiasm for attending school when these reopened.…”
Section: Parents Value and Trust Schoolsmentioning
confidence: 99%
“…The data show an increase in the number of children exposed to violence and witnessing domestic violence during the pandemic. Whereas, limited school activities and reduced direct contact with primary healthcare may cause a decrease in child abuse victims' identification (39)(40)(41).…”
Section: Mental Health and Development In The Communitymentioning
confidence: 99%